Inverted Polymer Solar Cells Using CdS Thin Film Grown by Successive Ionic Layer Adsorption and Reaction Method as Electron Transport Layer - Selcuk, M. Zeynep; Ongul, Fatih; Boroglu, Mehtap S.; Boz, Ismail; Yuksel, Sureyya Aydin (AMER SCIENTIFIC PUBLISHERS, 2017)
In this work, CdS thin films were coated by Successive Ionic Layer Adsorption and Reaction (SILAR) technique with various immersion cycles and used as electron transport layer (ETL). The effects of number of immersion cycle on the optical, structural and morphological properties of as prepared and annealed CdS films were investigated. The inverted type geometry hybrid solar cells were fabricated by using CdS films as electron transport layer (ETL), blend of P3HT(poly(3-hexyl) thiophene) and PCBM([6,6]-phenylC61 butyric acid methyl ester) as photoactive layer, and PEDOT:PSS:IPA and V2O5 films as hole transport layers (HTL). The power conversion efficiencies of the inverted hybrid solar cells were significantly enhanced by improved morphology, chemical composition of surface, optical properties of ETL and type of HTL.
Keywords: Cadmium Sulfide; Successive Ionic Layer Adsorption and Reaction Technique; Inverted Type Polymer Solar Cell; Electron Transport Layer; ORGANIC PHOTOVOLTAICS; SILAR METHOD; PERFORMANCE; EFFICIENCY; P3HTPCBM; Engineering; Science & Technology - Other Topics; Physics